2003
DOI: 10.1159/000075227
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Aquaporins in the Cochlea and Endolymphatic Sac of Guinea Pig

Abstract: It has been shown that the aquaporin (AQP) family forms membrane pores selectively permeable for water and some small solutes such as glycerol and urea, and thus plays important roles in regulating the fluid in many organs involved in fluid transport such as kidney, lung and brain. The aims of the present study were to investigate the cellular localization and its significance of aquaporins (AQPs) in various subregions of the cochlea and endolymphatic sac of guinea pig. The expression patterns of AQP1, 2, 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…AQPs 2, 3, 5, 7, 8, 9, and 10). However, previous studies have reported the expression of AQPs in the inner ear of several animal models (Fukushima et al 2004;Huang et al 2002;Merves et al 2003;Zhong and Liu 2003). For example, AQP2 is expressed in the endolymphatic sac of guinea pig and human (Couloigner et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQPs 2, 3, 5, 7, 8, 9, and 10). However, previous studies have reported the expression of AQPs in the inner ear of several animal models (Fukushima et al 2004;Huang et al 2002;Merves et al 2003;Zhong and Liu 2003). For example, AQP2 is expressed in the endolymphatic sac of guinea pig and human (Couloigner et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the inner ear, expression of AQPs 1, 2, 4, and 5 has been reported in the rat, mouse, and guinea pig (Beitz et al 1999(Beitz et al , 2003Huang et al 2002;Li and Verkam 2001;Merves et al 2003;Mhatre et al 1999Mhatre et al , 2002aMiyabe et al 2002;Sawada et al 2002Sawada et al , 2003Stankovic et al 1995;Takumi et al 1998;Zhong and Liu 2003). Dysfunction or lack of AQPs has been described in a variety of diseases, such as nephrogenic diabetes insipidus, early onset of cataract, Sjogren's syndrome, wet lung syndrome, congestive heart failure, and brain edema (for reviews, see Agre et al 2002;Agre and Kozone 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of aquaporin (AQP) water channels (Agre et al, 1993), it has become clear that these channels play a crucial role in water homeostasis not only in the kidney but also in the inner ear. Indeed, expressions of proteins and/or mRNAs of AQPs in the inner ear have already been reported including negative reports (AQP-1: Stankovic et al, 1995;Sawada et al, 2003;AQP2: Kumagami et al, 1998;Beitz et al, 1999;Merves et al, 2000;Mhatre et al, 2002;Sawada et al, 2002;Fukushima et al, 2005;Zhong and Liu, 2003;AQP-3: Beitz et al, 1999;AQP-4: Takumi et al, 1998;Minami et al, 1998;AQP-5: Beitz et al, 1999;Mhatre et al, 1999;Löwenheim and Hirt, 2004;AQP-6: Fukushima et al, 2002;Lopez et al, 2007;Taguchi et al, 2008;AQP-7: Beitz et al, 1999;Huang et al, 2002;AQP-8: Beitz et al, 1999;Huang et al, 2002;and AQP-9: Huang et al, 2002). However, previous reports have had many contradictions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the AQPs, isoforms 1-4 are the best studied in the inner ear and have been proposed to be involved in the pathophysiology of MD. AQP1 has been detected in the intermediate cells of the stria vascularis in rats and in nonsensory epithelial cells in the spiral ligament in humans [16][17][18]. Likewise, the immunolocalization of AQP4 in humans closely resembles the one seen in animal models [7,17,19].…”
Section: Introductionmentioning
confidence: 64%